The effect of cognitive emotion regulation strategies on gynecologic oncology: comparison between a clinical and a non-clinical sample - Junyi Wang; Ning Zhou; Danyang Wang; Ping Yu; Jing Xiao (Taylor & Francis Group, 2018)
Objective: This study aimed to examine the differences of cognitive emotion regulation (CER) strategies between patients with gynecologic cancer and non-clinical individuals. Methods: A cohort of 329 female adults was recruited in this study. About 179 patients with gynecologic cancer were allocated to the clinical group and 150 healthy women were allocated to the non-clinical group. All the participants completed a demographic survey and the Chinese version of Cognitive Emotion Regulation Questionnaire (CERQ-C). Results: There were statistically significant group differences in the CER strategies used between the two groups. The most prevalent discrepancies of the CER strategies across the two samples were the self-blame, rumination, putting into perspective, catastrophizing, and blaming others. Further logistic regression analyzes indicated that these four strategies have significant and independent contributions to the prediction of group membership. In particular, a higher reported use of self-blame and blaming others, and a lower reported use of acceptance and putting into perspective, were observed for the clinical group. The CER strategies in the clinical group, which differentiated it from the non-clinical group, accounted for 23.9% of the variance, after controlling for the non-dominant variables. Conclusion: The implications of certain CER strategies may be a useful target for prevention and intervention of psychological distress on patients with gynecologic cancer.